Unravelling the intertwined atomic and bulk nature of localised excitons by attosecond spectroscopy - Matteo Lucchini (Nature Portfolio, 2021)
The capability to follow electron motion in solids is necessary to explore the ultimate speed limits of optical charge manipulation and signal processing in optoelectronic devices. Here, the authors reveal the sub-femtosecond dynamics of core excitons in MgF2 and find the dual atomic-solid nature of the exciton quasi-particle to deeply affect its ultrafast dynamics.